The art of French piano music : Debussy, Ravel, Fauré, Chabrier - Howat, Roy (Yale University Press, 2009)
An essential resource for scholars and performers, this study by a world-renowned specialist illuminates the piano music of four major French composers, in comparative and reciprocal context. Howat explores the musical language and artistic ethos of this repertoire, juxtaposing structural analysis with editorial and performing issues. He also relates his four composers historically and stylistically to such predecessors as Chopin, Schumann, Liszt, the French harpsichord school, and Russian and Spanish music. Challenging long-held assumptions about performance practice, Howat elucidates the rhythmic vitality and invention inherent in French music. In granting Fauré and Chabrier equal consideration with Debussy and Ravel, he redresses a historic imbalance and reshapes our perceptions of this entire musical tradition. Outstanding historical documentation and analysis are supported by Howat's direct references to performing traditions shaped by the composers themselves. The book balances accessibility with scholarly and analytic rigor, combining a lifetime's scholarship with practical experience of teaching and the concert platform [Publisher's description].